2021
DOI: 10.1186/s41927-021-00190-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipoproteins and thyroid hormones with cognitive dysfunction in patients with systemic lupus erythematosus

Abstract: Background Neuropsychiatric manifestations occur in up to 75% of adult systemic lupus erythematosus (SLE) patients and are one of the major causes of death in SLE patients. Cognitive dysfunction is a typical clinical feature of neuropsychiatric SLE (NPSLE), which seriously affects the quality of life of patients. Dyslipidaemia and thyroid symptoms, which are prevalent in SLE patients, have both been related to neuropsychiatric disturbances, including significant psychiatric and cognitive distur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 94 publications
0
1
0
1
Order By: Relevance
“…The results of a Chinese study present a new perspective on thyroid hormones. It has been shown that F-T3 and F-T4 can be used as biomarkers of cognitive dysfunction in SLE patients, but this requires further research [91].…”
Section: Cognitive Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a Chinese study present a new perspective on thyroid hormones. It has been shown that F-T3 and F-T4 can be used as biomarkers of cognitive dysfunction in SLE patients, but this requires further research [91].…”
Section: Cognitive Disordersmentioning
confidence: 99%
“…Wyniki chińskiego badania ukazują nowe spojrzenie na hormony tarczycy. Wykazano, że F-T3 i F-T4 można stosować jako biomarkery dysfunkcji poznawczych u pacjentów z SLE, ale to wymaga dalszych badań [91].…”
Section: Zaburzenia Poznawczeunclassified